2022
DOI: 10.3390/app122211609
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Effects of Environmental Regulation and Financial Support for Agriculture on Agricultural Green Development: Spatial Spillover Effects and Spatio-Temporal Heterogeneity

Abstract: Environmental regulation and financial support for agriculture are regarded as important means to promote agricultural green development. Based on provincial panel data of 31 provinces in China between the years 2000 and 2020, this paper explores the interactive effect, spatial spillover effect and spatio-temporal heterogeneity of environmental regulation and financial support for agriculture on agricultural green development. The empirical conclusions are as follows: (1) The level of agricultural green develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…investigated the interactive effects of environmental regulation and fiscal support for agriculture on agricultural green development using provincial panel data from China. Their study concluded that the interaction between environmental regulation and fiscal support for agriculture had a positive spatial spillover effect on agricultural green development [34].…”
Section: Research On Factors Influencing Agricultural Green Developmentmentioning
confidence: 99%
“…investigated the interactive effects of environmental regulation and fiscal support for agriculture on agricultural green development using provincial panel data from China. Their study concluded that the interaction between environmental regulation and fiscal support for agriculture had a positive spatial spillover effect on agricultural green development [34].…”
Section: Research On Factors Influencing Agricultural Green Developmentmentioning
confidence: 99%
“…The agricultural Total factor productivity calculated by taking agricultural land, labor and machinery as input indicators and agricultural gross output value as output indicators represents high-quality agricultural development. On this basis, the output indicators added with carbon emissions represent green agricultural development [26]. Therefore, this paper uses the green total factor productivity of agriculture in 30 provinciallevel administrative regions (excluding Tibet, Hong Kong, Macao, and Taiwan) from 2001 to 2020 as a proxy variable for green agricultural development, mainly because the green total factor productivity of agriculture can be more accurately estimated by including agricultural resource factors and agricultural carbon emissions into the TFP growth measurement framework, and whether the agricultural economic development approach meets the "win-win" requirements of energy conservation and emission reduction and agricultural economic growth.…”
Section: Variable Selectionmentioning
confidence: 99%
“…On the other hand, environmental regulations are also considered as an important factor in promoting green development in agriculture [18]. Reasonable environmental regulation can promote the upgrading of local agricultural industry structure and technological innovation, and reduce agricultural pollution and agricultural carbon emissions [19]. However, strict environmental regulation will be higher than the input costs of agricultural development, which will not only fail to improve agricultural inefficiencies, but will instead exacerbate agricultural pollution in both local and neighboring areas [20,21], thus ultimately inhibiting the greening of agriculture in local and neighboring regions.…”
Section: Introductionmentioning
confidence: 99%